2021
DOI: 10.1152/ajpgi.00406.2020
|View full text |Cite
|
Sign up to set email alerts
|

Synapomorphic features of hepatic and pulmonary vasculatures include comparable purinergic signaling responses in host defense and modulation of inflammation

Abstract: Hepato-splanchnic and pulmonary vasculatures constitute synapomorphic, highly comparable networks integrated with the external environment. Given functionality related to obligatory requirements of "feeding and breathing", these organs are subject to constant environmental challenges entailing infectious risk, antigenic and xenobiotic exposures. Host responses to these stimuli need to be both protective and tightly regulated. These functions are facilitated by dualistic, high-low pressure blood supply of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 151 publications
1
6
0
Order By: Relevance
“…A compelling reason for these differences could be associated with different degrees of liver injury and, consequently, higher levels of cytotoxic molecules such as bile acids and bilirubin in the lung tissue. Moreover, complications such as gut permeability and the translocation of bacterial lipopolysaccharide as a potent activator of the inflammatory response are more prevalent in the later stages of cholestasis in the BDL model [31][32][33]. Hence, as observed in the current study, an enormous increase in lymphocytes, monocytes, neutrophils, IgG, TNF-α, IL-1β, and IL-6 in the BALF was observed on day 28 compared with day 14 after cholestasis induction.…”
Section: Agmatine Ameliorates Lung Inflammationsupporting
confidence: 69%
See 3 more Smart Citations
“…A compelling reason for these differences could be associated with different degrees of liver injury and, consequently, higher levels of cytotoxic molecules such as bile acids and bilirubin in the lung tissue. Moreover, complications such as gut permeability and the translocation of bacterial lipopolysaccharide as a potent activator of the inflammatory response are more prevalent in the later stages of cholestasis in the BDL model [31][32][33]. Hence, as observed in the current study, an enormous increase in lymphocytes, monocytes, neutrophils, IgG, TNF-α, IL-1β, and IL-6 in the BALF was observed on day 28 compared with day 14 after cholestasis induction.…”
Section: Agmatine Ameliorates Lung Inflammationsupporting
confidence: 69%
“…damage could develop into more severe complications, such as hepato-pulmonary syndrome, if not appropriately managed [31]. There is no specific pharmacological intervention against cholestasis-induced lung injury so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to PVR, another potential and untapped manifestation of PH is alteration of the gut microbiome and gut metabolic pathways, which have been demonstrated to be associated with a variety of cardiopulmonary diseases, including PH (Marsland et al, 2015;Tang & Hazen, 2017). Several previous studies have reported altered gut microbiome signatures in both patients with PH and numerous experimental PH animal models (Callejo et al, 2018;Hanidziar & Robson, 2021;Kim et al, 2020;Sharma, Oliveira, et al, 2020;Sharma, Stevens, et al, 2020), and gut microbiota elimination by a combination of antibiotics suppresses the development of PH in a SU5416/hypoxia-induced PH rat model (Sanada et al, 2020), indicating the potential lung-gut axis and essential roles of the gut microbiome in pulmonary vascular diseases. Interestingly, although SU5416/hypoxia, hypoxia-, and S. salivarius-induced PH produce obvious alterations in the composition of the gut microbiome, the specific changes are different, suggesting potentially different pathogenic mechanisms for these different PH models.…”
Section: Discussionmentioning
confidence: 99%